2019
DOI: 10.1038/s41598-019-40215-3
|View full text |Cite
|
Sign up to set email alerts
|

Poly ADP ribosylation and extracellular vesicle activity in rod photoreceptor degeneration

Abstract: Retinitis Pigmentosa is a group of inherited neurodegenerative diseases that result in selective cell death of photoreceptors. In the developed world, RP is regarded as the main cause of blindness among the working age population. The precise mechanisms eventually leading to cell death remain unknown and to date no adequate treatment for RP is available. Poly ADP ribose polymerase (PARP) over activity is involved in photoreceptor degeneration and pharmacological inhibition or genetic knock-down PARP1 activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Previous studies by Vidal-Gil et al (2019) report that the exosome protein marker CD9 was localized to the photoreceptor inner segments and ONL, further supporting a photoreceptor-origin hypothesis. However, it should be noted that CD9 was also found in the INL, GCL and choroid.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Previous studies by Vidal-Gil et al (2019) report that the exosome protein marker CD9 was localized to the photoreceptor inner segments and ONL, further supporting a photoreceptor-origin hypothesis. However, it should be noted that CD9 was also found in the INL, GCL and choroid.…”
Section: Discussionsupporting
confidence: 61%
“…However, it should be noted that CD9 was also found in the INL, GCL and choroid. Using a genetic model ( rd10 mice) of retinitis pigmentosa, which results in progressive rod photoreceptor-specific cell death ( Gargini et al, 2007 ; Vidal-Gil et al, 2019 ) showed that EVs isolated from retinal explants contain rhodopsin protein. This exosomal rhodopsin expression increased following photoreceptor rescue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This vesicle release is potentially a method to remove unwanted proteins during photoreceptor degeneration, when OS phagocytosis is compromised due to reduced OS transport of rhodopsin. Recent studies indicate that microvesicles are means of intercellular communication (Lee and Kim, 2017;Vidal-Gil et al, 2019). Contents of microvesicles, such as miRNA and signaling proteins, mediate phenotypic changes of the recipient cells (Schorey and Harding, 2016;Roballo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Retinitis pigmentosa (RP) is the most frequent hereditary retinal degenerative disorder in adults [68]. It causes a progressive loss of rod photoreceptors followed by a loss of cones [69].…”
Section: Retinitis Pigmentosa (Rp)mentioning
confidence: 99%